2016
DOI: 10.1002/2016jd025405
|View full text |Cite
|
Sign up to set email alerts
|

Impact of global warming on the rise of volcanic plumes and implications for future volcanic aerosol forcing

Abstract: Volcanic eruptions have a significant impact on climate when they inject sulfur gases into the stratosphere. The dynamics of eruption plumes is also affected by climate itself, as atmospheric stratification impacts plumes' height. We use an integral plume model to assess changes in volcanic plume maximum rise heights as a consequence of global warming, with atmospheric conditions from an ensemble of global climate models, using three representative concentration pathways (RCP) scenarios. Predicted changes in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 105 publications
(196 reference statements)
3
36
0
Order By: Relevance
“…Third, for model 3, the range of 6–8 found for βα in Figure is in remarkable agreement with the results of Aubry et al (), even though this previous study used an analytical scaling (relating plume height to source conditions and environmental parameters) and plume height measurement to constrain this ratio.…”
Section: Discussionsupporting
confidence: 89%
“…Third, for model 3, the range of 6–8 found for βα in Figure is in remarkable agreement with the results of Aubry et al (), even though this previous study used an analytical scaling (relating plume height to source conditions and environmental parameters) and plume height measurement to constrain this ratio.…”
Section: Discussionsupporting
confidence: 89%
“…Kipling et al [70] emphasized the importance of convective mixing controlling the aerosol vertical profile for all types except dust. Simulations using a plume model to assess future changes in volcanic aerosol transport suggest that a future increase in tropopause height due to strengthened convection will lead to reduced transport of volcanic aerosol into the stratosphere reducing its lifetime and cooling effect [71].…”
Section: Climate Impacts On Aerosol Transport and Depositionmentioning
confidence: 99%
“…For example, during the last glacial maximum (LGM, 21,000 years BP) there was a global 2-4-fold increase in the dust cycle intensity (Lambert et al 2015), which would have increased the albedo of the troposphere in a similar manner as for the future increase in manmade aerosols. Conversely, the global cooling of 3-5 • C relative to the pre-industrial during the LGM (Shakun et al 2012) would have lowered the tropopause by up to 1.5 km, so that smaller more frequent eruptions would more easily penetrate the stratosphere, following the mechanism outlined by Aubry et al (2016). Summers are nearly ice-free under RCP6 in 2050 in these simulations.…”
Section: Discussionmentioning
confidence: 97%
“…Although Aubry et al (2016) show that the amount of volcanic sulphur dioxide reaching the stratosphere is sensitive to climatic warming, they showed that this is effect is weakest for the largest eruptions. Therefore, it seems that for an eruption of the magnitude of Tambora, this is probably less important.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation